Operation of FCC with mixtures of regenerated and deactivated catalyst - Spretz, R. (2001)
The operation of FCC with mixtures of coked and regenerated catalyst was studied with a riser simulator reactor on two equilibrium catalysts at 550◦C. The coked catalysts maintain an activity level that enables them to be used in the mixtures. The catalytic performances of the regenerated catalysts were used as references against which the behaviors of 25:75 and 50:50 (coked:regenerated) mixtures were compared. It was observed that overall catoil has to be increased to maintain conversion. While the yields of gases, gasoline and LCO showed to be independent of the operative mode, changes were observed in the selectivity to light olefinsC4?C6that are mainly due to changes in the yields of the isoparaffins in the groups. In turn, these changes could be the consequence of the resulting density of paired acid sites in the zeolite components on hydrogen transfer reactions, due to the contributions by the coked and regenerated portions of catalysts. Coke yields in mixtures of coked and regenerated catalysts are not higher, which would allow increasing catalyst circulation without impacting on heat balance. The  particularities of this new operation of FCC are very dependent on catalyst properties.